Screening different microbial flora and their enzymatic activities during tea waste composting - Godishala, Akhila; Kumari, S. Chaitanya (International Journal of Scientific Research in Biological Sciences, 2019)
Proper management of solid waste is a major problem in most of the metropolitan areas. Composting is one of the oldest and simplest methods of organic waste stabilization. Composting tea waste is not only an environmental safe method of its disposal but also enhances the growth of the plants as it contains nutrients and tannic acid which create a more fertile environment. In the present study composting of tea waste with variations in type of soil, type of cattle dung and type of tea leaf waste was studied. From this physical, chemical, biological activities and soil enzymes such as cellulase, pectinase, proteases, amylases, xylanase activities were studied in various combinations like black soil, red soil, tea waste, green tea leaves waste along with cow dung, buffalo dung and goat manure in a ratio of 2:2:1 for a time period of 30 days. Analysis of soil with tea waste and cattle dung revealed that compost soil underwent changes in all measured physicochemical, biological and enzymatic parameters like moisture content recorded as 1.6%, highest temperature as 460 C and percentage of microbial population like bacteria as 60% and fungi as 40% were observed in the compost soil. Higher enzyme activities such as protease, pectinase, xylanase were observed with bacterial isolates comparatively with fungal isolates. PGPR activities such as IAA, Siderophore production, phosphate solubilization and organic acid production were also observed. Improved soil microbial and enzyme activities in cattle dung soil is an indication of improvement in soil fertility. Therefore the produced compost can be used to increase the crop yield and simultaneously decreasing the environmental pollution.